Compulsory Schooling Laws and Formation of Beliefs: Education, Religion and Superstition - Naci Mocan; Luiza Pogorelova (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
We exploit information on compulsory schooling reforms in 11 European countries, implemented mostly in the 1960s and 70s, to identify the impact of education on religious adherence and religious practices. Using micro data from the European Social Survey, conducted in various years between 2002 and 2013, we find consistently large negative effects of schooling on self-reported religiosity, social religious acts (attending religious services), as well as solitary religious acts (the frequency of praying). We also use data from European Values Survey to apply the same empirical design to analyze the impact of schooling on superstitious beliefs. We find that more education, due to increased mandatory years of schooling, reduces individuals' propensity to believe in the power of lucky charms and the tendency to take into account horoscopes in daily life.
Keywords: 330; Schulbesuch; Wirkungsanalyse; Bildungsniveau; Religionsgemeinschaft; Volksglaube; Soziale Werte; Schätzung; Europa